Normalization of Bilateral Relations between the USA and Myanmar (2008-2009) - PODBEREZNYKH, Inna E.; TSYPKO, Victoria V.; IVASYSHYNA, Nataliia V.; VASYLCHUK, Volodymyr M.; SIK, Kan-Den (Journal of Advanced Research in Law and Economics, 2019)
In the article, pre-conditions and circumstances of adjusting of bilateral relations are illuminated between the USA and Myanmar at the first administration of Barack Obama. The special attention is spared to the stages of bilateral relations of the USA with Myanmar from 2008 – 2009 and directions of their improvement. The theoretical and methodological basis of the article is a modern understanding of the principles and methods of historical research. The main ones are the method of comparative analysis, descriptive and historical retrospectives, which made it possible to reveal the essence of US bilateral relations with Myanmar in the post-bipolar period. The purpose of this article is to study the normalization of US-China relations during the first Obama administration. 2008 was decisive for American-Myanmar relations. The Obama administration was still able to focus attention and effort on the implementation of a number of tasks designed to promote successful implementation of an active, balanced and pragmatic policy in Myanmar. The reform process has brought great benefits and advantages for Myanmar. These benefits have been able to help stimulate the regime to continue the reform process. The reformers of Myanmar themselves are also confident that cooperation with the United States and its allies helped reduce the country's dependence on China. Washington played an important role in the democratization of Myanmar, and the Aung San Suu Kyi team was well aware of this in the country's international integration process.